Evolution of Sports with Artificial Intelligence - Rodrigues George; Madiwale Mohd Nauman (ITM Web of Conferences)
We cannot imagine things without AI in today’s world, everywhere and is playing a important role and today it’s a day where we can witness that slowly and steadily Artificial Intelligence creeping in into sports as well features like augmented reality and virtual reality are revolutionising the sports. This paper is about examining the impact of technology in sports performance analysis with focus on improving performance of athletes, improved decision making and improving the training methods. And also exploring the challenges of introducing technology into existing practise and also providing solutions to overcome the hurdles and emphasizes the role of DV, AI, VR and AR in revolutionizing the field. Also looking into the success stories of AI into nonsports industry and insights from sports science experts we are able to identify the challenges to apply technology like AI in Elite sports with focus in particular on AI controllability, Data collection an explainability of results. These findings are further more distilled into major key challenges faced by the community of sports analytics providing the road map for research in future and its application.